Catalyst‐Free S–S Bond Insertion Reaction of a Donor/Acceptor‐Free Carbene by a Radical Process: A Combined Experimental and Computational Study. Issue 22 (6th July 2016) - Zheng, Yang; Bian, Rongjian; Zhang, Xiaolu; Yao, Ruwei; Qiu, Lihua; Bao, Xiaoguang; Xu, Xinfang
Abstract : Herein, a donor/acceptor‐free carbene insertion reaction of an S–S bond through a radical process is presented. This catalyst‐free reaction was thermally induced and provided the dithioketal products in moderate to high yields. A mechanism involving radical intermediates was proposed according to the computational study, and these intermediates were verified experimentally and intercepted for the first time by using a cross‐coupling reaction. Abstract : A donor/acceptor‐free carbene insertion reaction of an S–S bond through a radical process is presented. This catalyst‐free reaction was thermally induced and provided the dithioketal products in moderate to high yields. A mechanism involving radical intermediates was proposed according to the computational study, and these intermediates were identified in a cross‐coupling reaction.